RANCANG BANGUN APLIKASI ABSENSI GURU MENGGUNAKAN GPS BERBASIS WEB RESPONSIVE ANDROID SMK NEGERI 1 RAMBAH - Rouza, Erni; Riki Mustafa, Satria; Basorudin; Wulandari, Yulia (Fakultas Ilmu Komputer, Universitas Pasir Pengaraian, 2023)
The discipline of the teacher's work includes an educator's obedience and observance of all the rules or regulations that have been enforced in the school with full consciousness from within. One example of the teacher's work discipline is his regular attendances. At Vocational high school (SMKN) 1 Rambah, the teacher attendance system is through an automatic attendance system that uses fingerprints, where teachers fill out attendance forms every day with a technology device that uses fingerprints as the user identification medium. Using fingerprint attendance machines at the time of the Covid-19 pandemic is very ineffective because fingerprinting tools touched by many people can cause the coronavirus to stick to the device and spread to the school environment. As a result, a new teacher attendance application must be designed and developed using a web-based GPS (Global Positioning System) and Android devices. This application is expected to break the COVID-19 transmission sequence. The application can be accepted and applied to SMK State 1 Rambah based on the results of testing using UAT (User Acceptance Testing)